2022
DOI: 10.1111/pde.15110
|View full text |Cite
|
Sign up to set email alerts
|

Association between obesity and atopic dermatitis in children: A case‐control study in a high obesity prevalence population

Abstract: Background/Objective: Atopic dermatitis (AD) is a chronic inflammatory skin disease.Research suggests an association between obesity and AD, although evidence is lacking from Latin American populations. This study evaluated the association of obesity with AD in children from Chile, a country with high obesity prevalence.Methods: A case-control study was performed in children with active AD (cases) and healthy controls (HCs) from Santiago, Chile. Body mass index was evaluated by z-score (z-BMI), with overweight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…AD was diagnosed based on the clinical examination using the UK’s Working Party diagnostic criteria [ 7 ], and disease severity was assessed using the Scoring Atopic Dermatitis Index (SCORAD), with cases being divided into mild (SCORAD <25), moderate (SCORAD 25-50) and severe (SCORAD >50) [ 8 ]. Quality of life impairment was evaluated in the AD group using the Dermatology Life Quality Index (DLQI) and its children’s version for children younger than 16 years [ 9 ]. Anthropometric parameters were evaluated in all participants: weight was measured in kilograms and height in centimeters; body mass index (BMI) was calculated as shown in equation 1:…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…AD was diagnosed based on the clinical examination using the UK’s Working Party diagnostic criteria [ 7 ], and disease severity was assessed using the Scoring Atopic Dermatitis Index (SCORAD), with cases being divided into mild (SCORAD <25), moderate (SCORAD 25-50) and severe (SCORAD >50) [ 8 ]. Quality of life impairment was evaluated in the AD group using the Dermatology Life Quality Index (DLQI) and its children’s version for children younger than 16 years [ 9 ]. Anthropometric parameters were evaluated in all participants: weight was measured in kilograms and height in centimeters; body mass index (BMI) was calculated as shown in equation 1:…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, obesity contributes to epidermal barrier dysfunction and has some shared risk factors with AD, such as poor diet and certain alterations in the intestinal microbiome [ 6 ]. Currently, data regarding the co-occurrence of AD and obesity or overweight status are controversial and debatable; some studies support this association [ 7 , 8 ], while others don’t [ 9 ]. However, studies have found a geographically variable association between obesity and AD in both children [ 10 ] and adults [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studies examining obesity in infancy and childhood also found a positive association with the prevalence of AD ( 13 , 14 ). Gender differences have been identified, as only females with AD had higher abdominal obesity rates than healthy controls ( 15 ). Leptin deficiency is commonly associated with obesity; however, conflicting studies suggest it may not be directly involved in AD pathogenesis ( 16 ).…”
Section: Atopic Dermatitismentioning
confidence: 99%